Influence of substitution at the 5α-Position on the side chain conformation of glucopyranosides. (February 2021) - Rajasekaran, Parasuraman; Pirrone, Michael G.; Crich, David
Abstract: We describe the preparation of methyl 5α-methyl-α-d -glucopyranoside and of 5α-fluoro-β-d -glucopyranose per acetate and the NMR-based conformational analysis of their side chains. Both the 5α-methyl and 5α-fluoro substituents increase the population of the gauche, gauche side chain conformer to the extent that it becomes the predominant conformation. In the 5α-methyl series this is attributed to steric effects, whereas in the 5α-fluoro series the optimization of attractive gauche effects is the more likely reason. Graphical abstract: Image 1 Highlights: Side chain conformation analysis of 5α-susbtituted glucopyranose derivatives. A 5α-methyl group strongly favors the gg side chain conformation of glucopyranosides. A 5α-fluoro substituent strongly favors the gg side chain conformation of glucopyranosides.